Pengaruh Performative Name Calling Service dan Credibility Content terhadap Keputusan Berkunjung melalui Electronic Word of Mouth pada Kedai Pinara Semarang - Muhammad Faiqul Ilmi; Nurhidayati Nurhidayati (Lembaga Yasin AlSys, 2026)
Intensifying competition in the culinary industry has encouraged business actors to develop experience-based and digital content–driven marketing strategies capable of capturing consumer attention, in line with the rise of viral marketing phenomena that combine creative on-site service with the dissemination of content via social media. This study aimed to analyze the influence of Performative Name Calling Service and Credibility Content on visiting decisions, with Electronic Word of Mouth (E-WOM) as an intervening variable at Kedai Pinara Semarang. A quantitative approach was employed using a survey of 100 respondents who were social media users and had previously viewed Kedai Pinara’s promotional content, selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed with the Partial Least Squares (PLS) method. The results showed that Performative Name Calling Service and Credibility Content had a positive and significant effect on E-WOM and visiting decisions. In addition, E-WOM had a positive and significant effect on visiting decisions and was able to mediate the influence of Performative Name Calling Service and Credibility Content on visiting decisions. These findings indicate that performative forms of service and credible digital content can strengthen online consumer-to-consumer communication, thereby increasing consumers’ interest in and decisions to visit. This study provides practical implications for culinary business actors to integrate unique service experiences with trustworthy digital content strategies to enhance consumer appeal and visitation.